2003
DOI: 10.1002/ca.10126
|View full text |Cite
|
Sign up to set email alerts
|

Tensile properties of fresh human calcaneal (achilles) tendons

Abstract: The purpose of this study was to measure the tensile properties of fresh human calcaneal (Achilles) tendons. Twenty fresh cadaveric (age range = 57-93 years) bone-Achilles tendon complexes were harvested within 24 hr postmortem. The calcaneus together with 15 cm of the Achilles tendon extending proximally from the insertion on the calcaneus was clamped and biomechanically tested. Each tendon was firmly fixed in clamps in an MTS Systems Corporation MTS testing machine and tension was applied at a displacement r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 27 publications
2
28
1
1
Order By: Relevance
“…For instance, although aligned scaffold demonstrated anisotropy similar to that of tendon tissue, improvements in tensile strength (*26 MPa) are clearly needed if intended to be used as a clinical tendon graft (*550 MPa). 58 In addition, functional in vivo implant likely requires a scaffold that sufficiently retains bioactive agents. For this purpose, scaffold surface modification may be carried out to immobilize bioactive macromolecules contained in tECM.…”
mentioning
confidence: 99%
“…For instance, although aligned scaffold demonstrated anisotropy similar to that of tendon tissue, improvements in tensile strength (*26 MPa) are clearly needed if intended to be used as a clinical tendon graft (*550 MPa). 58 In addition, functional in vivo implant likely requires a scaffold that sufficiently retains bioactive agents. For this purpose, scaffold surface modification may be carried out to immobilize bioactive macromolecules contained in tECM.…”
mentioning
confidence: 99%
“…However, their conclusions differ to large extent, which might cause some confusion for the readership and raises issues surrounding standardized testing of soft tissue material in anatomy and biomechanical research. While Liao et al (2015) reported decreased elasticity in six Thiel-fixed calcaneal tendons when compared with existing data on native ones (Louis-Ugbo et al, 2004;Verstraete et al, 2015) showed an increased Young's modulus in Thiel-embalmed calcaneal tendons compared with fresh ones from matched pairs. Both studies do have an apparent overlap in their data with loading rate-dependent properties ranging between 62.23 6 18.96 to 272.82 6 86.61 MPa (0.25%/s to 8%/s) (Liao et al, 2015) and 152.25 6 50.68 MPa (static loading with no further information given) (Verstraete et al, 2015), though the strains at which the material properties were computed were different.…”
mentioning
confidence: 78%
“…The generated forces ranged from 467.5 to 676.2 N. The stiffer tendon generated higher force at the Achilles tendon than the low-stiffness tendon, and the largest generated force was 1.45 times greater than the smallest one. , 2004, b: Rosager et al, 2002, c: Reeves et al, 2005 …”
Section: Effect Of Tendon Stiffness On the Generated Force At The Amentioning
confidence: 99%
“…(13) We selected some experimental results on the Achilles tendon material response from the several literatures (Louis- Ugbo et al, 2004;Rosager et al, 2002;Reeves et al, 2005;Shin et al, 2008), and identified the material parameters in Eq. (7), by using the least-squares method.…”
Section: 50e-5mentioning
confidence: 99%
See 1 more Smart Citation